2023
DOI: 10.1038/s41423-023-01013-0
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine monocyte chemoattractant protein-1/CCL2 is a promoter of breast cancer metastasis

Abstract: Breast cancer is the most prevalent cancer worldwide, and metastasis is the leading cause of death in cancer patients. Human monocyte chemoattractant protein-1 (MCP-1/CCL2) was isolated from the culture supernatants of not only mitogen-activated peripheral blood mononuclear leukocytes but also malignant glioma cells based on its in vitro chemotactic activity toward human monocytes. MCP-1 was subsequently found to be identical to a previously described tumor cell-derived chemotactic factor thought to be respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 193 publications
0
11
0
Order By: Relevance
“…Macrophage infiltration in breast cancer tumors is associated with tumor progression, metastasis, and poor prognosis . CCL2 is an important factor in tumor-associated macrophage accumulation and a promoter of breast cancer metastasis to the lungs and brain rather than to the bone. We therefore examined the expression of CCL2 in the lungs of the mice and found a significant decrease in the PD/Pep1 group compared with the other treatment groups, as shown by immunofluorescence (Figure D and Figure S29). It has been shown that the recruitment of inflammatory monocytes for CCR2, the receptor for the chemokine CCL2, and the subsequent recruitment of metastasis-associated macrophages and their interactions with metastatic tumor cells are dependent on CCL2 synthesized in the tumor and stroma .…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage infiltration in breast cancer tumors is associated with tumor progression, metastasis, and poor prognosis . CCL2 is an important factor in tumor-associated macrophage accumulation and a promoter of breast cancer metastasis to the lungs and brain rather than to the bone. We therefore examined the expression of CCL2 in the lungs of the mice and found a significant decrease in the PD/Pep1 group compared with the other treatment groups, as shown by immunofluorescence (Figure D and Figure S29). It has been shown that the recruitment of inflammatory monocytes for CCR2, the receptor for the chemokine CCL2, and the subsequent recruitment of metastasis-associated macrophages and their interactions with metastatic tumor cells are dependent on CCL2 synthesized in the tumor and stroma .…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that a dynamic and reciprocal relationship develops between cancer cells and components of the TIME that supports cancer cell survival, local invasion, and metastatic dissemination(26). Furthermore, upregulation of MCP-1, a potent monocyte-attracting chemokine, in the TIME could drive cancer development and progression via recruiting M2 macrophages within tumor microenvironment (26). Here we observe a rise in MALAT1 expression, correlating with increased levels of MCP-1 and CD68, CD163, CD206, indicative of M2 macrophages in tumor tissues of AA lung cancer patents.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, while numerous studies have documented the oncogenic function of MALAT1 in various tumors, its specific role in lung cancer among AAs had not been previously investigated. It is well accepted that a dynamic and reciprocal relationship develops between cancer cells and components of the TIME that supports cancer cell survival, local invasion, and metastatic dissemination(26). Furthermore, upregulation of MCP-1, a potent monocyte-attracting chemokine, in the TIME could drive cancer development and progression via recruiting M2 macrophages within tumor microenvironment (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations